From industrial to legal standardization, 1871-1914 : transnational insurance law and the great San Francisco earthquake - Röder, Tilmann J. (Legal history library. Studies in the history of private law ;, 2012)
Around 1900, standard contracts and clauses spread throughout international industries such as transport, insurance and finance. The ""earthquake clause"", which was globally introduced by reinsurers after the 1906 San Francisco catastrophe, exemplifies this paradigmatic change of the law.